The influence of ochratoxin A on DNA adduct formation by the carcinogen aristolochic acid in rats - Stiborová, Marie; Bárta, František; Levová, Kateřina; Hodek, Petr; Frei, Eva; Arlt, Volker M.; Schmeiser, Heinz H. (Archives of toxicology, 2015)
Exposure to the plant nephrotoxin and carcinogen aristolochic acid (AA) leads to the development of AA nephropathy, Balkan endemic nephropathy (BEN) and upper urothelial carcinoma (UUC) in humans. Beside AA, exposure to ochratoxin A (OTA) was linked to BEN. Although OTA was rejected as a factor for BEN/UUC, there is still no information whether the development of AA-induced BEN/UUC is influenced by OTA exposure. Therefore, we studied the influence of OTA on the genotoxicity of AA (AA-DNA adduct formation) in vivo. AA-DNA adducts were formed in liver and kidney of rats treated with AA or AA combined with OTA, but no OTA-related DNA adducts were detectable in rats treated with OTA alone or OTA combined with AA. Compared to rats treated with AA alone, AA-DNA adduct levels were 5.4- and 1.6-fold higher in liver and kidney, respectively, of rats treated with AA combined with OTA. Although AA and OTA induced NAD(P)H:quinone oxidoreductase (NQO1) activating AA to DNA adducts, their combined treatment did not lead to either higher NQO1 enzyme activity or higher AA-DNA adduct levels in ex vivo incubations. Oxidation of AA I (8-methoxy-6-nitrophenanthro[3,4-d]-1,3-dioxole-5-carboxylic acid) to its detoxification metabolite, 8-hydroxyaristolochic acid, was lower in microsomes from rats treated with AA and OTA, and this was paralleled by lower activities of cytochromes P450 1A1/2 and/or 2C11 in these microsomes. Our results indicate that a decrease in AA detoxification after combined exposure to AA and OTA leads to an increase in AA-DNA adduct formation in liver and kidney of rats.
Published online: 11 September 2014
Gesehen am 23.06.2020